2020
DOI: 10.15562/bmj.v9i1.1796
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis and its associated signalings

Abstract: Introduction: Melanogenesis is the mechanism of melanin formation in the skin or hair, which is produced by melanosomes in melanocytes. Melanin is the main coloring pigment of the skin, hair and eyes, and also functions as a photoprotection against ultra-violet (UV) exposure.Methods: A total 20 relevant literatures which focused on skin pigmentation and melanogenesis were used to construct this review. The articles were published from 1998-2018. Most of the literatures were basic research and the clinical info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The transcription factor MITF activates the expression of these melanogenic genes, inducing protein expression and regulating melanogenesis. Therefore, blocking MITF-related signaling pathways is considered an important strategy for developing melanogenesis inhibitors [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor MITF activates the expression of these melanogenic genes, inducing protein expression and regulating melanogenesis. Therefore, blocking MITF-related signaling pathways is considered an important strategy for developing melanogenesis inhibitors [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation exposure is considered to be the main cause of melanogenesis [ 3 ]. Furthermore, melanin is considered as the main determinant of hair, skin and eye colour, and has a vital function in protection against UV radiation [ 4 ]. However, it has been reported that UV radiation causes the overproduction of melanin, which leads to hyperpigmentation and other skin disorders such as ephelides (freckles), melasma, solar lentigines, pigmented acne scars, and cancer [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%